Design of Traction Convertor in 160 km/h RailwayEngineering Locomotive - FU Cheng-yong (机车电传动)
Traction converter principle, components and structure features of AC-drive 160 km/h railway engineering locomotive developed by CSR were introduced. Modularization and simplification idea was adopted for converter and inverter design, and mature parts and structure were applied to ensure product credibility, which decreased development risk and cost. The traction converter showed excellent performance and high reliability in 160 km/h railway engineering locomotive test, which satisfied new locomotive application requirement for railway engineering.